VR-Enabled Telepresence as a Bridge for People, Environments, and Experiences - Jones, Brennan; Zhang, Yaying; Wong, Priscilla N. Y.; Rintel, Sean; Heshmat, Yasamin (CHI 2020, 2020)
Rather than thinking of Virtual Reality (VR) as enabling geo-distant people to go to a common place, we have a more expansive view of VR as a bridge between people, environments, and experiences. We are interested in using VR and the related technology of Augmented Reality (AR), as tools to(1)bring a distant part of the physical world to someone, and (2) bring someone to a distant part of the physical world. This workshop paper discusses two design explorations we conducted to explore these subtle but important distinctions. We first discuss a unidirectional VR robotic telepresence interface that immerses a remote user in a distant environment, which was investigated for its value in outdoor exploration. We then discuss a bi-directional asymmetric VR-AR system that adds a photorealistic avatar for the remote user on to VR robotic telepresence. The avatar is viewed in third person by the local user as superimposed over the robot, and viewed in first person by the remote user. While the underlying technologies still need much development, we see promise in the ‘VR as bridge’ concept as a way to open up the design space to a critical need for flexible, diverse, and inclusive user needs.
Workshop on Social VR Workshop